The roles, procedures and effectiveness of internal shariah audit in the Malaysian Islamic banking industry. - Mohd Rushdan Yasoa’ (2022)
In order to seek blessings from Allah SWT, it is mandatory for the Islamic community to implement Islamic commercial jurisprudence (muamalat) in the business transactions. However, in the eagerness of Islamic banks (IBs) in providing those products and services to customers, they sometimes have overlooked the existence of Shariah non-compliance (SNC) cases. The SNC cases occur due to the lack of control in identifying and mitigating these SNC cases at the individual bank level. In the long run, this SNC may affect stakeholders' perception of Islamic banking operations and eventually lead to a severe loss of trust. Hence, this study investigates the roles, procedures, and factors perceived to contribute to internal Shariah audit (ISA) effectiveness in IBs. A qualitative approach through in-depth interviews among nine practitioners, including Shariah auditors (SAR) in IBs, is conducted. The data have been transcribed and coded according to several themes and analyzed using Atlas.ti software, version 8.0. The findings reveal that the role of SAR is to provide assurance to shareholders and stakeholders on Shariah compliance of IBs’ operations. They also look into the internal control element in preventing any possible Shariah breaches. However, SAR’s roles have changed gradually in the sense that the roles are much broader and cover all aspects of businesses and operations. In terms of Shariah audit procedures, most interviewees highlight that the approach is significantly changing from compliance audit to risk-based audit. On the ISA effectiveness factors’ perspective, the interviews' findings confirmed the previous studies that the SAR's competence, SAR's independence, and management support are the main determinants that contribute to the ISA effectiveness. The other two new variables suggested in this study, namely Islamic accountability and Shariah Committee (SC) support, are perceived by the interviewees as the new determinants contributing to the ISA effectiveness. Additionally, this study also successfully discourses the issues and challenges that the ISA is facing, such as the SAR competencies’ issues, the external Shariah audit (ESA) services, and the need for the ISA framework. The study contributes to the body of the knowledge by proposing that SAR's competence, SAR’s independence, management support, Islamic accountability, and SC support contribute to the ISA effectiveness. Thus, to ensure that the ISA is effective, IBs should ensure that these factors are closely monitored. The researcher acknowledges this study's limitation with regard to the inability to interview the relevant expertise such as the financial regulator due to unavailability of interviewees. Future research may consider conducting a focus group interview to produce more comprehensive results. It is hoped that in enhancing the roles, procedures, and ISA effectiveness, IBs will consider all those factors and promote the Shariah compliance environment while upholding Al Maqasid As Shariah in the Islamic banking industry.